Pengaruh Service Quality dan Price terhadap Kepuasan Konsumen Warung Sasak Ayu Lestari di Kota Mataram - Ernia Ayu Lestari; Hilmiati Hilmiati (TSAQOFAH, 2026)
Consumer satisfaction is an important aspect of culinary business sustainability because it is influenced by service quality and the perceived appropriateness of prices. This study aims to analyze the effect of service quality and price on consumer satisfaction at Warung Sasak Ayu Lestari in Mataram City. This study used a quantitative approach with an associative research design. The research sample consisted of 100 respondents selected using purposive sampling. Data were collected through a questionnaire and then analyzed using validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and the coefficient of determination (R²). The results show that, partially, service quality had a positive and significant effect on consumer satisfaction, with a calculated t value of 4.861 > t table of 1.9847. The price variable also had a positive and significant effect on consumer satisfaction, with a calculated t value of 6.571 > t table of 1.9847, and was the most dominant variable. The conclusion of this study emphasizes that service quality and price play an important role in increasing consumer satisfaction, with price as the most dominant factor. These findings imply the need for better management of service quality and more appropriate pricing strategies to strengthen consumer satisfaction at Warung Sasak Ayu Lestari in Mataram City.